The Relationship between Corporate Governance, Employee Salaries, Salary Gaps and Financial Performance - Ming-Chuan Wang,; Shen-Yuan Chen,; Shih-Wei Hung, (Asian Academy of Management Journal of Accounting and Finance, 2024)
Given the scarcity of literature exploring the nexus between corporate governance and employee salaries, this study investigates the impact of corporate governance on employee compensation and its subsequent effects on financial performance. We identify a positive correlation between robust corporate governance and higher employee salaries, which in turn enhances firm profitability and value. Our findings also suggest that employee salaries act as a partially mediate in the relationship between corporate governance and firm value, indicating a nuanced mechanism through which governance quality influences organisational outcomes. Notably, we observe that enhanced corporate governance is associated with a wider salary gap between management and non-management employees, a factor that might adversely affect financial performance. These results underscore the complex dynamics between corporate governance and employee compensation strategies, contributing to a deeper understanding of their interplay.